Diversity and Distribution of Freshwater Fishes of the Dano, Banganga, and Arung Khola Rivers of Western Nepal - Shrestha, Santoshi; Khatri, Kumar; Shrestha, Nripesh; Poudel, Ram Chandra; Sapkota, Kumar (Banko Janakari, 2025)
This study was conducted to generate foundational data on the fish diversity of three rivers in western Nepal. Three sampling sites were selected on each of the following rivers: the Dano River, the Banganga River, and the Arung Khola. Cast netting was conducted with the help of local fishermen during the post-monsoon, winter, and pre-monsoon seasons from 2018 to 2022. A total of 52 species belonging to 7 orders, 16 families, and 36 genera were recorded. Cypriniformes was the most dominant order across all river systems. Garra simbalbaraensis and Glyptothorax striatus were reported as new species for Nepal. The most abundant species were Garra gotyla in the Dano River and Puntius sophore in both the Banganga and Arung Khola. In contrast, Schismatorhynchos nukta and Glyptothorax striatus were each observed only once. The Dano River exhibited the highest species richness and diversity, suggesting more heterogeneous habitat with a balanced species distribution. All three river systems showed relatively high evenness, indicating that species were evenly distributed across the sampling sites. These findings provide vital baseline data and underscore the importance of continued research to monitor biodiversity trends and to support evidence-based conservation and management strategies for sustaining freshwater ecosystems in western Nepal.